The effect of the multimodal intervention on blood pressure in patients with first ischemic stroke: A randomized controlled trial - Orapin Jullmusi; Jintana Yunibhand; Chanokporn Jitpanya (Belitung Raya Foundation, Indonesia, 2023)
Background: Multimodal intervention is currently promoted to control blood pressure in patients with first ischemic stroke. However, a dearth of studies has examined the influence of the intervention among patients with ischemic stroke, particularly in Thailand. Objective: This study aimed to determine the effect of the multimodal intervention on blood pressure in patients with first ischemic stroke. Methods: A randomized controlled trial was conducted. Sixty participants were randomly selected from two tertiary hospitals in Thailand. Eligible participants were randomly assigned into an experimental group (n = 30) and a control group (n = 30). The experimental group was provided with the multimodal intervention, while the control group was given the usual care. Data were collected from May 2021 to October 2021 at baseline (pre-test), 4th week, 8th week, and 12th week using the demographic data form and sphygmomanometer. The data were analyzed using the Chi-square test, t-test, and repeated measure analysis of variance (ANOVA). Results: The participants’ blood pressures after receiving the multimodal intervention were lower than those before receiving the multimodal intervention. Both systolic and diastolic blood pressure were statistically significantly decreased over time, starting from baseline to the 8th week and 12th week (p <0.001). In addition, the participants’ mean scores of systolic blood pressure (F (1, 58) = 4.059, p = 0.049) and diastolic blood pressure (F (1, 58) = 4.515, p = 0.038) were lower than the control group. Conclusion: The multimodal intervention is effective in controlling blood pressure. Therefore, nurses should educate patients with ischemic stroke to manage systolic and diastolic blood pressure, facilitate the patient’s participation in the exercise program, and monitor the patients via telephone to continue blood pressure control. Trial Registry: Thai Clinical Trials Registry (TCTR) identifier number 20210318001.